The jury system - Hull, B.R. (My University, 1897)
Introduction: Like all other great social institutions, our present jury system did not spring into existence all at once, but was a process of gradual evolution. Consequently authorities differ as regards its origin. Some claim it is of Frankish origin and dates back to 978; others think it developed from the early judicial customs of the Teutonic people; while Blackstone says it was among the earliest Saxon colonies. The Magna Carta provides that no man shall be deprived of his life or property except through a verdict of his peers. Whatever be its origin the first case we have recorded in English history is during the reign of Henry II. It probably, however, made its appearance in England soon after the Norman Conquest. During the reign of Henry II we find juries of two kinds: “Juries of Inquest” and “Grand Juries”. The juries of inquest had to do only with civil cases. The plaintiff would get four sworn knights from his district, they would close twelve more and the sixteen would sit as judges. In case of disagreement new juries might be chosen until a unanimous decision was rendered.
Citation: Hull, B.R. The jury system. Senior thesis, Kansas State Agricultural College, 1897.
Morse Department of Special Collections
Keywords: Jurisprudence; Legal system; Theses; Manuscripts (documents)